Publisher Correction: Associations between subjective well-being and subcortical brain volumes. Issue 1 (December 2018) - van 't Ent, D.; Braber, A.; Baselmans, B.; Brouwer, R.; Dolan, C.; Pol, H.; Geus, E.; Bartels, M.
A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has not been fixed in the paper.